Structural evolution induced preferential occupancy of designated cation sites by Eu2+ in M5(Si3O9)2 (M = Sr, Ba, Y, Mn) phosphors. Issue 62 (14th June 2016) - Wei, Yi.; Lin, Chun Che; Quan, Zewei; Molokeev, Maxim S.; Atuchin, Victor V.; Chan, Ting-Shan; Liang, Yujun; Lin, Jun; Li, Guogang
Abstract : A schematic presentation for the unexpected blue-shifted luminescence of Eu 2+ in M5 (Si3 O9 )2 (M = Sr, Ba, Y, Eu, Mn) based on the preferential occupancy at the designated cation sites. Abstract : In this paper, we present new insight into a changing Eu 2+ crystallographic site preference in Eu-doped M5 (Si3 O9 )2 (M = Sr, Ba, Y, Mn), which is related to the structural variation induced by M cation substitutions. The effect of the local structural geometry on the luminescence properties of Eu 2+ is revealed. By substitution of Ba 2+ for Sr 2+, the lattice expansion is restricted to specific cation sites, resulting in the abrupt blue shifted emission of Eu 2+ ions. The abnormal blue shift on replacing Sr 2+ with Mn 2+ is attributed to the preferential 6-fold coordination for Mn 2+ that moves the Eu 2+ ions to other sites. The results elucidate the mechanisms of emission band adjustment by local site coordination change and it can be potentially extended to crystals which properties are sensitive to local lattice variations.